Phytochemistry, Pharmacological Potential, and Ethnomedicinal Relevance of Achillea nobilis and Its Subspecies: A Comprehensive Review - Anastassiya Shevchenko; Aiman Аkhelova; Shamshabanu Nokerbek; Aigul Kaldybayeva; Lyazzat Sagyndykova; Karlygash Raganina; Raushan Dossymbekova; Aliya Meldebekova; Akerke Amirkhanova; Yerbol Ikhsanov; Gulzhan Sauranbayeva; Manshuk Kamalova; et al. (Molecules)
Achillea nobilis and its subspecies (A. nobilis subsp. neilreichii and A. nobilis subsp. sipylea) have been traditionally used in various ethnomedical systems across Eurasia. However, comprehensive studies on their phytochemical composition and pharmacological properties are still insufficient. This review aims to provide a critical synthesis of current knowledge regarding the botanical characteristics, geographic distribution, traditional applications, chemical constituents, and pharmacological effects of A. nobilis A structured search was conducted using eight scientific platforms, including Scopus, PubMed, Web of Science, Google Scholar, Science.gov, ScienceDirect, JSTOR, and BASE. Keywords related to phytochemistry, pharmacology, and ethnomedicine were applied, and a total of 28,000 records were initially retrieved. After a multi-stage screening process based on inclusion and exclusion criteria, 167 peer-reviewed publications from 1952 to 2023 were selected for detailed evaluation. Findings reveal a diverse range of bioactive compounds, such as flavonoids, monoterpenes, sesquiterpenes, and sesquiterpene lactones, which demonstrate antioxidant, antimicrobial, anti-inflammatory, antinociceptive, antispasmodic, and anticonvulsant activities. Most studies have focused on aerial parts and water-based extracts, while the root chemistry and organ-specific metabolite profiles remain largely unexplored. This review highlights the therapeutic potential of A. nobilis and underscores the need for future studies using multi-omics and advanced analytical techniques to support its development in pharmaceutical and nutraceutical applications.